Secoisolariciresinol diglukozid (SDG) izololovan iz lana u prevenciji i liječenju dijabetes melitusa: Management of diabetes with SDG - Prasad, Kailash; Bhanumathy, Kalpana Kalyanasunderam (Scripta Medica, 2023)
This review focuses on the role of reactive oxygen species (ROS) on the development of type 1 and type 2 diabetes and its treatment with secoisolariciresinol diglucoside (SDG) isolated from flaxseed which is an antioxidant and suppresses phosphoenolpyruvate carboxykinase (PEPCK) gene expression, a rate- limiting enzyme in the gluconeogenesis in the liver. Role of ROS in the development of type 1 diabetes [diabetic prone Bio Breeding (BBdp) rats and streptozotocin-induced diabetic (STZ) rats and type 2 diabetes (Zucker diabetic fatty female rats, ZDF rats)] has been discussed. Oxidative stress has been assessed by measuring serum and pancreatic malondialdehyde (MDA), pancreatic chemiluminescence (pancreatic-CL) and oxygen radical producing activity of white blood cells (WBC-CL). Diagnosis of diabetes was made by hyperglycaemia and glucosuria. Incidence of diabetes was 100 % in SDZ rats, 72 % in BBdp rats and 100 % in ZDF rats by the age of 72 days. Development of diabetes was associated with increases in the serum and pancreatic MDA, WBC-CL and pancreatic-CL and glycated haemoglobin (HbA1c). SDG prevented the development of diabetes by 75 % in STZ rats, by 71 % in BBdp rats and by 20 % at 72 days of age in ZDF rats. However, 80 % of the rats which did not develop diabetes by 72 days of age, developed diabetes later on, suggesting that SDG treatment delays the development of diabetes in ZDF rats. Treatment with SDG decreased the levels of serum and pancreatic MDA, WBC-CL and pancreatic-CL. In conclusion, development of type 1 and type 2 diabetes is mediated through oxidative stress and the prevention or delay in the development of diabetes with SDG could be due to its antioxidant activity and its suppressant effect on PEPCK enzyme. Lignan complex which contains 34 % to 38 % of SDG is effective in lowering serum glucose and HbA1c in type 2 diabetes in humans.